KONSEP KESEJAHTERAAN PANDANGAN ULAMA KONTOMPORER - Nur Arifin; Tamimah; Nida Laili Fitriyah (Program Studi Perbankan Syariah STAI Al-Fitrah Surabaya, 2021)
Islamic economics, one of which aims to prosper people's lives, human welfare stated in the Qur'an is related to human enjoyment and misery in the world and the hereafter, development can be achieved if aspects of economic sovereignty and good economic governance can be realized significantly because it builds economic sovereignty, this research uses qualitative research using literature studies, the results of this study, welfare in the Islamic perspective refers to the goals of Islam, namely the implementation and maintenance of the five basic principles contained in Maqasid Syariah from everything that is destructive so as to achieve a better life and honorable in this world and in the hereafter. Keywords: Development Economics, Welfare, Maqasid Syariah.